(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Education, as a phenomenon in society, the participation of the growing generation in society’s life, life, social production activity, creativity and spirituality is a complex contradictory socio-historical process. In school and in the course of extracurricular activities, students’ mutual respect and moral qualities are formed among the team. In this, the culture of students’ behavior towards each other is formed. It will be discussed about the role of parents in organizing extracurricular activities.